Refikite from Krásno, Czech Republic: a crystal-and molecular-structure study. (2nd January 2018) - Pažout, Richard; Sejkora, Jiři´; Maixner, Jaroslav; Dušek, Michal; Tvrdý, Jaromír
Abstract: The crystal structure of the organic mineral refikite has been determined. The mineral was found in joints in bark and wood from pine trees in the 'V Borkách' peat deposit near the town of Krásno, Slavkovský les Mountains, western Bohemia, Czech Republic. It forms white to light-yellow polycrystalline crusts or randomly intergrown, transparent, colourless, very thin, acicular crystals up to 0.2–0.5 mm long. Sometimes, colourless-to-white elongated prismatic crystals up to 1 –1 .5 mm in size were encountered. The mineral is soft (Mohs hardness ∼1) and very brittle, with an uneven fracture. No visible cleavage was discerned. Crystals have a greasy-to-glassy lustre; fine crystal aggregates have a pearly lustre. Refikite, empirical formula C20 H34 O2 or C19 H33 COOH, is a derivative of abietic acid. It is orthorhombic, space group P 21 21 2, with a = 22.6520(7), b = 10.3328(3), c = 7.6711(2) Å, V = 1795.49(9) Å 3, Z = 4. Refikite comprises two closely related compounds based on perhydrophenanthrene. The major component has two axial methyl groups, one terminal carboxylic group and one terminal propan-2-yl (isopropyl) group joined to the three fused rings in the same fashion as in abietic acid. However, the fused ring system is fully reduced (contains single bonds only). In the minor component, the terminal propan-2-yl group is replaced by a propen-2-yl (methylvinyl) group. The crystal structure is stabilized by strong O···H–O hydrogen bonds. High-resolution mass spectroscopy (HRMS) confirmed a molecular mass of 306 and the formula C20 H34 O2 . Hydrogen-1 and carbon-13 nuclear magnetic resonance (NMR) spectroscopy showed the presence of four methyl groups in the major component; infrared (IR), Raman and NMR spectra are consistent with the structure. The HRMS, IR and Raman spectroscopy methods confirmed the presence of a minor component containing the propen-2-yl group replacing the propan-2-yl group. This is also reflected in a shortened C15–C17 single bond metric of 1.468(6) Å shown by single-crystal X-ray analysis. The trivial name of the major component of refikite is tetrahydroabietic acid or abietan-18-oic acid. This work represents the first proof of the existence of abietic acid derivatives as naturally occurring species.